2012
DOI: 10.1152/ajprenal.00583.2011
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal dopamine modulates progressive angiotensin II-mediated renal injury

Abstract: It is well-recognized that excessive angiotensin II (ANG II) can mediate progressive renal injury. Previous studies by us and others have indicated that dopamine may modulate actions of ANG II in the kidney. The current studies investigated whether altering intrarenal dopamine levels affected ANG II-mediated renal fibrosis. We utilized a model of increased intrarenal dopamine, catechol-O-methyl-transferase knockout (COMT KO) mice, which have increased kidney dopamine levels due to deletion of a major intrarena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 40 publications
1
40
0
2
Order By: Relevance
“…Systemic chronic infusion of ANG II induces the overexpression of fibronectin and collagen I deposition in the kidney (52). Some of the ANG II-dependent mechanisms involved in the development of CKD involve oxidative stress, intrarenal RAS overactivation, and high blood pressure (11,21,46).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chronic infusion of ANG II induces the overexpression of fibronectin and collagen I deposition in the kidney (52). Some of the ANG II-dependent mechanisms involved in the development of CKD involve oxidative stress, intrarenal RAS overactivation, and high blood pressure (11,21,46).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha mostrado que, al envejecer, una exagerada función de los receptores renales AGTR1 está asociada con una disminución en la función del receptor DRD1 y con niveles elevados de presión arterial en modelos de ratón (90). Además, el efecto natriurético de DRD1 es potenciado durante el bloqueo de los receptores AGTR1 (91); y la dopamina, por medio de sus acciones en los receptores DRD1, disminuye la expresión del AGTR1 y los sitios de unión de la angiotensina II en las células del túbulo proximal renal (92,93).…”
Section: Discussionunclassified
“…Examples of epithelial stress are ER stress, dysregulation of energy metabolism, G2/M cell cycle arrest (104), autophagy apoptosis, and necrosis (Table 1). Recent studies support the idea that the diseased epithelial cell alone is sufficient to drive fibrosis and CKD (35,105). By using genetic tools to express the human diphtheria toxin receptor only on tubule epithelial cells (35), the investigators showed that repeated selective proximal tubule cell ablation led to interstitial fibrosis, glomerulosclerosis, and capillary rarefaction.…”
Section: Contribution Of Other Cells To Fibrogenesismentioning
confidence: 97%